Conjunto de testes de garantia de qualidade de um software para planejamento radioterápico - Schmidt, Giovana Tamiozzo (2014)
Radiotherapy can be highlighted as one possible treatment of cancer. From this point of view, the planning system for radiotherapic treatment is crucial. In order to check the software for the computerized planning of the Cobalt-60 equipment, a series of tests was defined following the standards given by the: TEC DOC 1151 protocol " Aspectos Físicos da Garantia de Qualidade em Radioterapia, Protocolo de Controle de Qualidade (TEC DOC 1151, 2000), o Technical Reports Series Number 430 (TRS 430) (IAEA, 2004), o TRS 398 Absorbed Dose Determination in External Beam Radiotherapy: An International Code of Practice for Dosimetry based on Standards of Absorbed Dose to Water (TRS 398, 2004). The depth dose of interest of the acrylic simulators used to control the quality of computerized tomography were evaluated, tests of the software and hardware as well as the input and output of data were analyzed, tests of the boundary conditions, of the percetual dose and of the field profile were also performed. An analysis of the results show that the performance of the software results was satisfactory. The only deviattions appeared in the field profile tests that do not fulfilled the expectations due to the limitations of the system.